Developmental disabilities across the world: A scientometric review from 1936 to 2020. (October 2021) - Carollo, Alessandro; Bonassi, Andrea; Lim, Mengyu; Gabrieli, Giulio; Setoh, Peipei; Dimitriou, Dagmara; Aryadoust, Vahid; Esposito, Gianluca
Highlights: A scientometric review was conducted on 11, 315 documents available on Scopus. Four research domains were identified qualitatively from the documents' keywords. One documents co-citation analysis was conducted on each of the research domain. Trends in the research from 1936 to 2020 were identified and discussed in detail. The leading contribute of North America to the existing literature emerged. Abstract: Background: Developmental disabilities have been largely studied in the past years. Their etiological mechanisms have been underpinned to the interactions between genetic and environmental factors. These factors show variability across the world. Thus, it is important to understand where the set of knowledge obtained on developmental disabilities originates from and whether it is generalizable to low- and middle-income countries. Aims: This study aims to understand the origins of the available literature on developmental disabilities, keeping a focus on parenting, and identify the main trend of research. Methods and Procedure: A sample of 11, 315 publications from 1936 to 2020 were collected from Scopus and a graphical country analysis was conducted. Furthermore, a qualitative approach enabled the clustering of references by keywords into four main areas: "Expression of the disorder", "Physiological Factors", "How it is studied" and "Environmental factors". For each area, a document co-citation analysis (DCA) on CiteSpace software was performed. Outcomes and Results: Results highlight the leading role of North America in the study of developmental disabilities. Trends in the literature and the documents' scientific relevance are discussed in details. Conclusions and Implications: Results demand for investigation in different socio-economical settings to generalize our knowledge. What this paper adds? The current paper tries to provide insight into the origins of the literature on developmental disabilities with a focus on parenting, together with an analysis of the trends of research in the field. The paper consisted of a multi-disciplinary and multi-method review. In fact, the review tried to integrate the analysis of the relation between developmental disabilities with a closer look at the scientific contributions to the field across the world. Specifically, the paper integrates a total of 11, 315 papers published on almost a century of research (from 1936 to 2020). An initial qualitative analysis on keywords was combined to a subsequent quantitative approach in order to maximize the comprehension of the impact of almost a century of scientific contributions. Specifically, documents were studied with temporal and structural metrics on a scientometric approach. This allowed the exploration of patterns within the literature available on Scopus in a quantitative way. This method not only assessed the importance of single documents within the network. As a matter of fact, the document co-citation analysis used on CiteSpace software provided insight into the relations existing between multiple documents in the field of research. As a result, the leading role of North America in the literature of developmental disabilities and parenting emerged. This was accompanied by the review of the main trends of research within the existing literature.